PENGOLAHAN MINUMAN SEHAT SUJEL UNTUK MENINGKATKAN PENGHASILAN UMKM MASYARAKAT DESA TAPIAN NAULI I - Delita Sihotang; Hadijah Sipahutar; Indra Setiawan Hutabarat; Heriyawan Hutagalung; Alfansuri Tanjung (LLPM Universitas Deli Sumatera, 2024)
One of the tri dharma of higher education is that lecturers are required to do community service. STIE Al Washliyah Sibolga supports lecturers in carrying out community service according to their areas of expertise. One of the areas of expertise at STIE Al Washliyah Sibolga is related to entrepreneurship. Basically, the purpose of community service is to provide new ideas about entrepreneurship and build a creative and entrepreneurial spirit, especially for young people at Desa Tapian Nauli I. The targeted result with dedication is to provide entrepreneurship counseling to build a creative and entrepreneurial spirit for beginners. The expected creative abilities are creative and innovative abilities which form the basis of an entrepreneurial spirit to achieve success. The entrepreneurial spirit can encourage an independent, creative and innovative mentality, be responsible and not give up easily when starting a business. It is hoped that this counseling will run well and the insight of young people at Desa Tapian Nauli I will increase.